Music Teaching Curriculum Integrates Physical Exercise to Regulate Students’ Mental Health - Zhao Liu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Efficiently conducting scientifically-grounded sports activities and harnessing the full potential of physical education in enhancing students' physical and mental well-being represents an area of active inquiry among educators. Addressing the imperative of enhancing physical exercise to regulate students' mental health, an investigative initiative advocating for the integration of physical exercise within a music teaching curriculum was proposed. The study employed an experimental research design, involving a survey conducted among 580 first and second-grade students at an experimental middle school within an urban setting. Out of the distributed 580 questionnaires, 530 valid responses were collected, comprising 280 male and 250 female students, resulting in a recovery rate of 93%. Both questionnaire and interview surveys were utilized during data collection, with the questionnaire survey serving as the primary method. Among the 530 valid responses obtained, findings revealed that 70% of middle school students exhibited good mental health, while 40% reported experiencing mild mental issues, 10% had moderate mental challenges, 2.4% demonstrated severe mental problems, and 0.8% exhibited extremely severe mental issues. Employing music therapy within music classroom instruction holds potential to enhance the mental health education of adolescents and elevate their psychological well-being. This practice contributes to fostering a positive classroom culture for school principals, facilitates effective student management, and enhances students' psychological resilience. The integration of music therapy into music education significantly impacts the holistic development of junior high school students' mental health. Notably, music instruction in junior middle schools inherently encompasses a plethora of teaching elements conducive to mental health education. In accordance with the nuanced dynamics of students' physical and psychological maturation, educators must diligently explore teaching resources, employ effective pedagogical approaches, engage in meaningful student dialogue, and prioritize the holistic well-being of students. This entails guiding students to cultivate a healthy psychological disposition aligned with the developmental trajectories of their physical and mental states, thereby enhancing their overall psychological resilience and character development. Music assumes a pivotal and multifaceted role in fostering the mental health development of junior high school students. Through the process of musical appreciation and learning, students are continually inspired to persevere, engage in proactive self-development, and endeavour to realize their life aspirations, ideals, and values.